Is a small-caliber or large-caliber endoscope more suitable for colonic self-expandable metallic stent placement? A randomized controlled study. (January 2022) - Minoda, Yosuke; Ogino, Haruei; Sumida, Yorinobu; Osoegawa, Takashi; Itaba, Soichi; Hashimoto, Norikazu; Esaki, Mitsuru; Kitagawa, Yusuke; Yodoe, Kentaro; Iboshi, Yoichiro; Matsuguchi, Takahiro; Tadokoro, Mei; et al.
Objectives: The colonic self-expandable metallic stent (C-SEMS) with a 9-French (Fr) delivery system allows for a small-caliber endoscope (SCE) to be used to treat malignant colonic obstruction. Despite the lack of evidence, the SCE has become popular because it is considered easier to insert than the large-caliber endoscope (LCE). We aimed to determine whether the SCE is more suitable than the LCE for C-SEMS placement. Methods: Between July 2018 and November 2019, 50 consecutive patients who were scheduled to undergo C-SEMS for colon obstruction were recruited in this study. Patients were randomized to the SCE or LCE group. The SCE and LCE were used with 9-Fr and 10-Fr delivery systems, respectively. The primary outcome was the total procedure time. Secondary outcomes were the technical success rate, complication rate, clinical success rate, insertion time, guidewire-passage time, stent-deployment time, and colonic obstruction-scoring-system score. Results: Forty-five patients (SCE group, n = 22; LCE group, n = 23) were analyzed. The procedure time in the LCE group (median, 20.5 min) was significantly ( p = 0.024) shorter than that in the SCE group (median, 25.1 min). The insertion time in the LCE group (median, 2.0 min) was significantly ( p = 0.0049) shorter than that in the SCE group (median, 6.0 min). A sub-analysis of the procedure difficulties showed that the insertion time in the LCE group (median, 5.0 min) was significantly shorter than that in the SCE group (median, 8.5 min). Conclusion: Both LCE and SCE can be used for C-SEMS; however, LCE is more suitable than SCE as it achieved a faster and equally efficacious C-SEMS placement as that of SCE. Clinical trial registration number: University Hospital Medical Information Network Clinical Trials Registry (UMIN 32748)